BIOLOGI REPRODUKSI DAN FAKTOR KONDISI IKAN ILAT-ILAT, Cynoglossus bilineatus (Lac. 1802) (PISCES: CYNOGLOSSIDAE) DI PERAIRAN PANTAI MAYANGAN JAWA BARAT - Ahmad Zahid; Charles P.H. Simanjuntak (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2009)
The reproductive biology and length-weight relationship of fourlined tonguesole, (Cynoglossus bilineatus Lacapede, 1802) were examined in the Mayangan Coast, West Java from May to November 2003. The objective research was describe some aspect reproductive such as sex ratio, spawning season, fecundity, and spawning type; and also describe length-weight relationship and condition factor. The total length (TL) of all observed specimens ranged from 80 to 369 mm. Sex ratio of males and females was 1.5:1. Fecundity of this species was estimated at between 2.323 and 225.557 eggs per individual. C. bilineatus is an asynchronous, partial spawner, with are spawning peaks in June and September (for males), July and October (for females). Negative allometric was established in the length-weight relationship (b=2.859). Condition was estimated at between 0.89 and 1.06 for males and 0.84-1.08 for females.